Stude of water-oil emulsion using wave treatment dispersant - A. A. Baubek; A. M. Gribkov; M. G. Zhumagulov; S. A. Glazyrin; M. V. Dolgov (Известия высших учебных заведений: Проблемы энергетики, 2021)
THE PURPOSE. To develop an apparatus for wave treatment of water-fuel oil and preparation of water-fuel emulsion for combustion. To present a scheme of an innovative vortex burner device for water-oil emulsion combustion. To review existing equipment for preparation of high quality emulsion. Refute the necessity of forced dehydration of fuel oil for high-quality combustion in burners. To present data on the choice of material for manufacturing the dispersant body, taking into account the requirements for corrosion resistance, as well as resistance to cavitation and wear resistance. To develop an experimental setup for the preparation of water-oil emulsion for combustion in a vortex burner. To conduct an analysis to identify the relationship of transformation of physical and chemical properties of water-oil emulsion (sedimentation and aggregative stability, structural viscosity) from temperature and volume of water in them. METHODS. Theoretical methods of viscosity and density determination were used in solving the problem and results were obtained experimentally, by using a capillary viscometer, in different temperature ranges of emulsified fuel preparation. A method was used to assess the clarification of the WFE to evaluate the sedimentation stability, with compulsory conditioning in glass cylinders in a statistical state. RESULTS. The preparation of WOE is conditioned by the water content rationing. The factor of partial loss of moisture at the plant during emulsion preparation can be considered as a positive side effect of dewatering. Data on the density of water-oil emulsion depending on the concentration of water at 70 0C has been obtained. The analysis of dependence of stability of emulsion based on fuel oil M-100 from time of settling at 20 0C is made. CONCLUSION. The presented wave dispersant experimentally demonstrates a high quality of VME preparation. Experimental results prove the presence of a significant numerical increase of the 10 μm particle size, as well as a minimum conversion of 1.25 μm particles towards the 2.5 μm particle size. The use of wave treatment dispersant results in stable water-oil emulsions suitable for use as fuels in the power industry.